ANALISIS PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN AGROINDUSTRI SAGU DI KABUPATEN KOLAKA TIMUR - Tuti Karmyati; Marsuki Iswandi; La Rianda (Jurnal Sosio Agribisnis, 2018)
Empowering farmers is an important thing amid many agricultural problems and farmers powerlessness to expand their agricultural business. It is hoped that a development of sago agroindustry can increase farmers’ potentials and in turn improve their welfares. This study aimed to: analyze the empowerment of farmers who process the sago; analyze the level employment in the development of sago; analyze the level of incomes earned by the sago- processing  farmers. The study was conducted in the village of Tinengi, at the district of Tinondo in East Kolaka Regency. Population of the study was farmers who processed sago. Sampels were determined using a purposive method. Results of the study show that an association of sago-processing farmers is made up several groups of non-formal sago-processing business. In actuality, the number of employment created in the sago processing business is 493 HOK/ha/years, whereas if the sago land area is increased to 2 hectares, the amount of labor that can be absorbed is 1120 HOK /year. Sago processing farmers' income on a land area of 1 hectare is Rp 1.170.438,-/month, but if the sago land area is increased to 2 hectares, the income increases to Rp 5.521.533,-/month..Keywords: empowering; development of sago; employment; income